Truss topology optimization of timber–steel structures for reduced embodied carbon design. (1st February 2022) - Ching, Ernest; Carstensen, Josephine V.
Abstract: There is an increasing need for automated design processes that can help guide structural design towards lower embodied carbon solutions. This research presents a two-material truss topology optimization algorithm that aims at reducing the Global Warming Potential (GWP) of the designed structure. The ground structure approach is used and a new set of design variables are defined such that both the cross-sectional area and the material composition of each truss element is determined. The framework is developed for several different objective and constraint functions. These include designing for a minimum compliance objective with either weight or GWP constraints, and minimizing the GWP with stress constraints. The framework is demonstrated on truss designs with a mix of glue-laminated timber (GLT) and steel elements for both 2D and 3D design examples. Highlights: Two-material truss topology optimization that limits the embodied carbon is introduced. The design frameworks are demonstrated on 2D and 3D timber–steel examples. New design variables are introduced to optimize both member size and material. Single material structures are obtained if not considering stress constraints. Better performing structures are produced when modifying the material stress limits.